Possible biocontrol of bacterial blight in pomegranate using native endophytic Bacillus spp. under field conditions - Manjunatha, N.; Pokhare, Somnath S.; Agarrwal, Ruchi; Singh, Nripendra V.; Sharma, Jyotsana; Harsur, Mallikarjun M.; Marathe, Rajiv A. (Frontiers in Microbiology, 2024)
Bacterial blight in pomegranate, caused by Xanthomonas citri pv. punicae (Xcp), is one of the most devastating diseases, leading to substantial economic losses in pomegranate production. Methods for blight management in pomegranate production are scarce and not well established. To date, the major control strategy is targeting the pathogen with antibiotics and copper-based compounds. However, excessive use of antibiotics has resulted in the development of antibiotic resistance in the field population of Xcp. Hence, as a means of eco-friendly and sustainable management of bacterial blight, the use of native endophytes was investigated under field conditions in the current study. Endophytic bacteria were isolated from micro-propagated nodal explants of pomegranate and were identified as Bacillus haynesii, B. tequilensis, and B. subtilis. They were found to produce volatiles that inhibited Xcp growth during in vitro antibiosis assay. GC–MS-based volatile profiling revealed the presence of several bioactive compounds with reported antimicrobial activities. These endophytes (CFU of 108/mL) were then spray-inoculated on leaves of 6-month-old pomegranate plants in the polyhouse. They were found to induce ROS-scavenging enzymes such as catalase and peroxidase. This alteration was a manifestation of host tissue colonization by the endophytes as ROS scavenging is one of the mechanisms by which endophytes colonize the host plants. Furthermore, two-season field trials with endophytes for blight control resulted in a reduction of disease index by 47–68%, which was considerably higher than the reduction due to the chemical immune modulator (2-bromo-2-nitro-1, 3-propanediol) currently being recommended for blight control. In addition, these endophytes also exhibited reduced sensitivity to this immune modulator; thus, the current study advocates the use of B. haynesii, B. subtilis, and B. tequilensis as biocontrol agents for bacterial blight of pomegranate either alone or as a part of integrated disease management.